The effect of climate at origin on Douglas-fir growth, leaf traits and embolism resistance along a rainfall gradient in Central Europe - Vincent P. Riedel; Patrick Engel; Pierre-André Waite; Roman M. Link; Randolf Schirmer; Joachim Hamberger; Bernhard Schuldt (Trees, 2025)
Key message In Douglas-fir grown in Central Europe, growth and specific leaf area differed between coastal and interior provenances but little intra-specific variability was found for the Huber value and xylem safety. Abstract In Central Europe, the economically most important timber species for roundwood production, Norway spruce, has been severely affected by recent global change-type drought events. Due to its large spatial distribution, Douglas-fir ( Pseudotsuga menziesii ) is considered for conversion to climate-resilient forests. Specifically, provenances from moister coastal and drier and colder interior regions might differ in drought tolerance traits. Here, we characterized aboveground biomass increment as well as leaf morphological and plant hydraulic traits in mature trees of 28 Douglas-fir provenances from three climate-at-origin groups across a climatic gradient in Central Europe, covering a precipitation range of 542 mm yr −1 . Irrespective of the gradient, the northern interior provenances had a 5.4 kg yr −1 lower aboveground biomass increment than the two coastal groups, accompanied by a 13% smaller specific leaf area. On the other hand, the Huber value, embolism resistance ( P 50 ) and leaf carbon isotope signature (δ 13 C) as proxy for long-term intrinsic water use efficiency did not differ between climate-origin groups. Across the gradient and within a climate-origin-group, no effect of climatic aridity on any of the traits covered was observed. Especially P 50 showed very little intra-specific variability, and our observed mean of −3.5 MPa is in the same range as P 50 -values for Douglas-fir recently reported from Europe. Our results for Douglas-fir support that xylem safety is a rather conservative and evolutionary canalized trait in conifers, while the Huber value revealed less plasticity as expected. Future studies are needed to test whether slower-growing interior provenances with thicker and smaller needles might be more drought tolerant and thus better suited for cultivation in the future climate of Central Europe although xylem safety does not differ.